Study of mental states in online classes caused by COVID-19, using brain-computer Interface - Rojas Romero, Kain Corina (2021)
The pandemic caused by COVID-19, has achieved the confinement of people around the world, changing many habits and customs. Education is one of the areas where this aspect has caused many changes in the way of studying, mainly in the physical place where the classes are received, in the educational process they went from studying in a classroom to a room in the house And in many cases in the classroom, this new way of studying is causing changes in many aspects, one of the most important and which is the object of this study are changes in the levels of attention provided by students, because they are being affected by agents. distractors such as television, family members among others. The present work focuses on being able to analyze how the concentration and meditation levels are presenting at the time they do their classes, these measurements are made through a brain-computer interface, where the brain signals are recorded and presents concentration and meditation in a range of 0 to 100%, the results show that the children present a low level of concentration at the beginning and at the end of the class sessions, the maximum attention values are presented between 10 to 15 minutes of classes with values above 80%.